Continent in dust : experiments in a Chinese weather system - Zee, Jerry C., 1985- (Critical environments (Oakland, Calif.), 2021)
Continent in Dust explores material permutations of sand and wind--the life and course of a Chinese dust storm, though successive phases of matter--as sites of political, anthropological, and scientific experiment. It moves from science stations, forestry and social management schemes, and sand-threatened cities in China's desertified interior, to the particulate politics of air-spacing in a dust-shocked Beijing, to the technical and political challenges of international meteorological exposures in Korea and the US, China's downwind. The manuscript offers an intervention into the political anthropology of Reform China and a new approach to studying environmental crisis as a site of social, economic, and geophysical conflict"--